Effectiveness of pregnant women's class on the success of exclusive breastfeeding - Indrawati Aris Tyarini; Yoga Tri Wijayanti; Asridawati Akib; Nofita Tudang Rombeallo; Sitti Zakiyyah Putri (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Exclusive breastfeeding (EBF) during the first six months of life plays a crucial role in infant survival, growth, and development. However, the global rates of EBF remain below the recommended targets. Pregnant women's classes are designed to provide education, support, and skills necessary for successful breastfeeding practices. This study aimed to analyze the effectiveness of pregnant women's classes on the success rate of exclusive breastfeeding. Methods: A quasi-experimental design with a posttest-only control group was employed. The study involved 120 pregnant women in their third trimester, selected through purposive sampling from two community health centers. The intervention group (n=60) participated in a structured pregnant women's class, while the control group (n=60) received standard antenatal care without additional courses. Data on breastfeeding practices were collected three months postpartum using structured interviews and analyzed using the Chi-square test and logistic regression. Results: The study found a significantly higher rate of exclusive breastfeeding in the intervention group (78.3%) compared to the control group (53.3%) (p<0.01). Attendance in the pregnant women's class was associated with a 2.9 times higher likelihood of practicing exclusive breastfeeding (OR=2.9; 95% CI: 1.5–5.6). Key factors contributing to success included increased maternal knowledge, self-efficacy, and support from health educators during antenatal. Conclusions: Participation in pregnant women's classes effectively increases the success rate of exclusive breastfeeding. Integrating structured breastfeeding education into routine antenatal care is recommended to improve maternal practices and promote better infant health outcomes